دور محاسبة التسيير في قياس الأداء المالي للمؤسسة الاقتصادية - كردوسي, محمد (جامعة الوادي - University of Eloued, 2020)
تهدف هذه الدراسة إلى معرفة دور محاسبة التسيير في قياس الأداء المالي للمؤسسة الاقتصادية، خاصة بعد النتائج التي حققتها أساليب محاسبة التسيير الحديثة في المؤسسات الخدمية و الاقتصادية، بعدما عجزت الأساليب التقليدية على مواكبة التطور في بيئة التصنيع الحديثة و أصبحت أثار عجز هذه الأساليب لا يمكن تجاهلها من قبل المنشآت الموجودة على اختلاف أنواعها و أحجامها الذي أثر عليها بشكل كبير ، فأصبح من الضروري على هذه المنشآت اتخاذ أساليب تسييريه حديثة التي تمكنها من ضبط إنتاجها من خلال تخفيض التكلفة و التخلص من الأنشطة التي لا تضيف قيمة على منتوج المنشآت، و الذي سوف يؤثر في تحسين الأداء المالي للمؤسسات الاقتصادية، ويمكنها في الصمود في البيئة المعاصرة و تحقيق الميزة التنافسية لها، تم الاعتماد في هذه الدراسة على المنهج الوصفي التحليلي من أجل عرض المعلومات المتعلقة بمحاسبة التسيير و الأداء المالي للمؤسسة الاقتصادية، والدور الذي تلعبه محاسبة التسيير في قياس الأداء المالي. This study aims to know the role of management accounting in measuring the financial performance of an economic institution, especially after the results achieved by modern management accounting methods in service and economic institutions, after traditional methods have struggled to keep pace with the development in the modern manufacturing environment, and the effects of the deficiency of these methods cannot be ignored by existing establishments of different types and sizes that have affected them greatly, It became necessary for these establishments to adopt modern management methods that enable them to control their production by reducing costs and getting rid of activities that do not add value to the enterprises' product, which will affect the improvement of the financial performance of economic institutions, and can resist in the contemporary environment and achieve Its competitive advantage. This study relied on the descriptive and analytical approach in order to present information related to management accounting and the financial performance of the economic institution, and the role that management accounting plays in measuring financial performance
The role of management accounting in measuring the financial performance of the economic institution
مقال
Keywords: محاسبة التسيير ; الوظيفة المالية ; قياس الأداء ; الأداء المالي ; التحليل المالي ; المؤسسة الاقتصادية